2017
DOI: 10.1021/acs.jafc.7b04688
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Compounds of Edible Purple Laver Porphyra sp. (Nori)

Abstract: Porphyra sp. (nori) is widely cultivated as an important marine crop. Dried nori contains numerous nutrients, including vitamin B, which is the only vitamin absent from plant-derived food sources. Vegetarian diets are low in iron and vitamin B; depletion of both causes severe anemia. Nori also contains large amounts of iron compared with other plant-derived foods and eicosapentaenoic acid, which is an important fatty acid found in fish oils. In nori, there are also many bioactive compounds that exhibit various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 81 publications
0
53
0
3
Order By: Relevance
“…Crustaceans, such as shrimp, lobster, and crab, have frequently been involved in immunoglobulin E‐mediated allergies. Therefore, that study suggested that dried nori products could potentially cause severe allergic reactions, particularly in crustacean‐allergic persons (Bito, Teng, & Watanabe, ).…”
Section: Resultsmentioning
confidence: 99%
“…Crustaceans, such as shrimp, lobster, and crab, have frequently been involved in immunoglobulin E‐mediated allergies. Therefore, that study suggested that dried nori products could potentially cause severe allergic reactions, particularly in crustacean‐allergic persons (Bito, Teng, & Watanabe, ).…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, studies of other edible seaweeds (e.g., green or brown algae) focused mainly on their non-food roles as sources of nutraceuticals, food additives, and biomaterials. Nutritional values and bioactive components of algal species linked to major health benefits were reported, highlighting the potential for growth of the laver industry as both an edible seaweed and a source of useful compounds [4,[9][10][11][12][13][14][15][16][17][18]. However, although practical studies of the utility of laver as an edible seaweed reported the distinct characteristics of various product types (i.e., material composition, effects of manufacturing processes), there is no comprehensive analysis of the literature regarding the nutritional/functional characteristics of laver and the technological basis for its quality control.…”
Section: Genus Speciesmentioning
confidence: 99%
“…Lavers can be a component of other food products such as seaweed chips, salads, laverbread, laver cake, onigiri (rice ball), kimbab (seasoned rice roll), and laver soup [10,13,15,16]. However, previous studies of these processed products focused on organoleptic characteristics with sensory evaluation, rather than on potential for health and/or nutritional benefits.…”
Section: Processed Laver Productsmentioning
confidence: 99%
See 2 more Smart Citations